Chromospheric Heating by Magnetohydrodynamic Waves and Instabilities. Issue 6 (1st June 2021) - Srivastava, A. K.; Ballester, J. L.; Cally, P. S.; Carlsson, M.; Goossens, M.; Jess, D. B.; Khomenko, E.; Mathioudakis, M.; Murawski, K.; Zaqarashvili, T. V.
Abstract: The importance of the chromosphere in the mass and energy transport within the solar atmosphere is now widely recognized. This review discusses the physics of magnetohydrodynamic waves and instabilities in large‐scale chromospheric structures as well as in magnetic flux tubes. We highlight a number of key observational aspects that have helped our understanding of the role of the solar chromosphere in various dynamic processes and wave phenomena, and the heating scenario of the solar chromosphere is also discussed. The review focuses on the physics of waves and invokes the basics of plasma instabilities in the context of this important layer of the solar atmosphere. Potential implications, future trends and outstanding questions are also delineated. Key Points: Physics of waves in solar chromosphere Heating of the chromosphere by waves and instabilities Wave propagation through the solar chromosphere